Parties and Politics in America - Rossiter, Clinton, 1917-1970 (Book collections on Project MUSE., 1960)
A distinguished historian and political scientist provides a forthright and objective account of American party politics in this concise and invaluable guide. In vigorous and lively language he examines the two major parties-"the peacemakers of the American community"--Describing their historic functions and the way they have helped to achieve national unity. He discusses their make-up, their achievements and failures, the images each has established of itself and of the opposition party. The demographic forces influencing the American voter and the complex question of how the parties actually differ receive thought-provoking treatment. This invigorating analysis of the hard facts of American political life will live far beyond the election year of 1960